The Effect of Work Environment, Work Discipline, and Motivation on Employee Performance: A Case Study of Sanctoo Suites & Villas, Gianyar Regency - Anak Agung Mira Shylla Putri; Sapta Rini Widyawati; Ni Putu Ayu Sintya Saraswati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
This study aims to determine the influence of work environment, work discipline, and work motivation on employee performance at Sanctoo Suites & Villas Gianyar Regency. This study is associative in nature. The population in this study consisted of all 45 employees of Sanctoo Suites & Villas Gianyar Regency. The sampling technique used was Saturation Sampling Technique, where the entire population in this study was taken as a sample. The data analysis technique used was multiple linear regression analysis. The results showed that the work environment had a positive and significant effect on employee performance at Sanctoo Suites & Villas in Gianyar Regency, meaning that the better the work environment, the better the employee performance would be. Work discipline has a positive and significant effect on employee performance at Sanctoo Suites & Villas in Gianyar Regency, meaning that the better the work discipline, the better the employee performance will be. Work motivation has a positive and significant effect on employee performance at Sanctoo Suites & Villas in Gianyar Regency, meaning that the better the work motivation, the better the employee performance will be.